Experience of Contraceptive Denial, Perceived Ease of Future Access to Contraception, and Adverse Mental Health Outcomes in Polish Women - Jade M; Mijas ME; Jasienska G; Galbarczyk A (International Journal of Women's Health)
Morgan Jade,1 Magdalena Ewa Mijas,2 Grazyna Jasienska,2 Andrzej Galbarczyk2,3 1School of Health and Related Research, University of Sheffield, Sheffield, UK; 2Department of Environmental Health, Faculty of Health Sciences, Jagiellonian University Medical College, Krakow, Poland; 3Department of Human Behavior, Ecology and Culture, Max Planck Institute for Evolutionary Anthropology, Leipzig, GermanyCorrespondence: Andrzej Galbarczyk, Department of Environmental Health, Jagiellonian University Medical College, 8 Skawinska St., Krakow, 31-066, Poland, Tel +48 693 02 55 27, Fax +48 12 632 48 81, Email agalbarczyk@gmail.comPurpose: While several studies demonstrate an association between reproductive coercion or a lack of reproductive autonomy and decreased mental health in women, little is known about potential mental health impacts when women are denied prescription contraceptives. The aim of this research was to explore associations between prescription contraceptive denial and perceived ease of future access to contraception, and self-assessed mental health.Patients and Methods: Polish women (N=424) completed an anonymous online survey with demographic questions; perceived stress (PSS-10), state anxiety (STAI-X1), and depression (CESD-R) assessments, and contraceptive access questions.Results: Eighty-eight participants (21%) had experienced at least one episode of prescription contraceptive denial from a doctor or pharmacist. There were no differences in stress, anxiety, and depression scores between women who had and had not ever experienced denial. However, women who had experienced contraceptive denial within the last six months, had higher depression scores. In addition, women who perceived future access as very easy had the lowest stress, anxiety and depression scores.Conclusion: These results suggest that experiences and attitudes related to contraceptive access are related to perceived stress, anxiety, and depression. Contraceptive denial and other access barriers constitute a significant public health issue that may impact the health of women.Keywords: conscientious objection, reproductive autonomy, sexual health, reproductive coercion